Current state of the problem of urogenital mycoplasma infection - L. A. Yusupovа; E. I. Yunusovа; Z. Sh. Garaeva; G. I. Mavlutova; D. N. Novikova (Лечащий Врач)
The article presents data on urogenital Mycoplasma infection. Etiological and pathogenic mechanisms leading to the development of the disease, risk factors for urogenital Mycoplasma infection are described in detail. The data on clinical manifestations of the disease, including in children and adolescents, the effect of Mycoplasma infection on the reproductive function of men and women are presented. The article reveals information about the diagnosis and therapy of Mycoplasma infection of the urogenital tract.